Event Flash Sale Terhadap Keputusan Belanja Online Selama Pandemi Covid-19 Pada Marketplace Serta Implikasi Pada Kepuasan Konsumen di Kota Malang - Rachmadi, Kartika Rose; Arifin, Rois (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2021)
Covid-19 pandemic in Indonesia requires business people to innovate in business. Not only one or two sectors but many sectors, one of which is the business and trade sector, which causes their income to decline. The state of this pandemic is one of the driving factors for the creation of competition for all sectors, and in this case, business people. One of is the sales promotion program like flash sale event, including the marketplace. In the other hand, it can also see how online shopping behavior at flash sales events and its effect on consumer satisfaction. The research method uses quantitative using explanatory research techniques involving 200 respondents with accidental sampling. Distribution of questionnaires using Google forms while still paying attention to government policies in the form of social distancing and psbb. The results showed that the three variables in this study such as flash sales, online shopping decisions and satisfaction had a significant positive effect on the marketplace during the pandemic in Malang City.